Business Potential of Arctic Berry Wax in the beauty industry of California, USA - Taskila, Joel; Mikkola, Jonne (Oulun ammattikorkeakoulu, 2018)
Universities from Finland, Sweden and Norway have a joint project on examining the extraction, properties and marketing opportunities for a new wax made from the skin and leaves of wild-grown lingonberries. This thesis focuses on market potential of this new ingredient in the state of California, United States. The wax is not produced on an industrial scale and the research on its features and benefits is on-going or it is not published yet. The chosen research method for this thesis is desktop research. There is no Arctic Berry Wax based product on the market at all yet, but none the less the market potential was examined through existing trends of the cosmetics market. The trends relevant for this research were vegan, organic and cruelty-free. Lingonberry, the ingredient for Arctic Berry Wax is carefully studied through its known health benefits and sosio-economic effect. The most common waxes in cosmetics were studied and their relation to chosen trends. These trends were examined through social media channels and statistics. A research on how well these trending properties outstand on existing products were examined and defined. On theory part the potential of Arctic Berry Wax was examined through market opportunity analysis, defining customer value and market demand. Based on the results and findings the business potential might be there, but the Arctic Berry Wax does not stand out from the other waxes. On cosmetics industry the cruelty free and vegan are not enough to stand out. Organic cosmetics on an industrial scale is very hard to execute, but there is something to be further researched. On thesis writers’ opinion the business potential could be obtained by further research on possible health benefits of Arctic Berry Wax. The der-matology and healthy cosmetics might be the right direction because the lingonberry itself has a lot of proven health benefits. The purity of Scandinavian nature could be used for marketing pur-poses. Our conclusion on the topic is, that the most important thing there should ...